The Shifting of Regional Regime: Study Case of Renegotiation NAFTA to USMCA - Putri Febrianty Ardhana; Rahmah Daniah (Institute of International Studies, 2022)
This study was designed using descriptive writing techniques using secondary data with library research techniques and qualitative analysis. The results of this study indicate that the factors behind the renegotiation of NAFTA to the USMCA come from internal and external factors. From internal factors, there are considerations from each NAFTA member country in the form of profit and loss considerations from an economic perspective, such as gains from Foreign Direct Investment (FDI) and losses in the form of trade deficits. Meanwhile, from external factors, there were considerations related to the existence of economic threats from third parties, several NAFTA rules that are considered detrimental and irrelevant, as well as considerations of the potential for modernizing NAFTA rules from a digital trade perspective. In addition, the renegotiation of NAFTA to the USMCA also brings those international agreements to a deeper stage of economic integration, where the USMCA is between the Free Trade Agreement (FTA) and Customs Union stages because the USMCA has deeper rules than the FTA stage. However, on the other hand, it still does not fully comply with the rules at the stage of the Customs Union.